Penerapan Metode Bermain Peran dalam Mengembangkan Karakter Disiplin pada Siswa Kelas III Mata Pelajaran Ppkn pada Materi Nilai-Nilai Pancasila SDIT Raudhatur Rahmah Pekanbaru - Nanda Putri Maileni; Wismanto Wismanto; Deprizon Deprizon; Salman Salman; Sakban Sakban; Radhiyatul Fithri (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Disciplinary character is an attitude and feeling of being obedient and obedient to values ​​that are believed to be one's responsibility. Therefore, teachers try to develop students' disciplined character, one of which is by applying the role-playing method. This research aims to develop students' disciplined character through role-playing methods on Pancasila values. This researcher uses a qualitative method with the Classroom Action Research (PTK) type, which consists of 2 cycles and each cycle has 2 meetings. The data collection techniques are through observation, interviews and documentation. The research results obtained from the application of the role playing method in PPKN subjects on Pancasila values ​​for teachers in cycle I increased from 75.5% to cycle II 88.75%. The application of the role playing method in PPKN subjects regarding Pancasila values ​​to students in cycle I was 67.5% and cycle II was 93.75%. Meanwhile, student learning outcomes in the mathematics subject material flat shapes after implementing the picture and picture model increased with the average score in cycle I being 65% and cycle II being 85%.